2015
DOI: 10.1039/c5ra09864e
|View full text |Cite
|
Sign up to set email alerts
|

Third order NLO properties of corannulene and its Li-doped dimers: effect of concave–convex and convex–convex structures

Abstract: The convex–convex stacking motif of corannulene dimers enhances the third-order NLO response due to obvious interlayer charge transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…To the best of our knowledge, the ⟨ R 2 ⟩ is used to characterize the electron density volume around the molecule as a physical property. The more diffuse electron cloud may lead to a larger ⟨ R 2 ⟩ value, resulting in a larger α value. , …”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, the ⟨ R 2 ⟩ is used to characterize the electron density volume around the molecule as a physical property. The more diffuse electron cloud may lead to a larger ⟨ R 2 ⟩ value, resulting in a larger α value. , …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of our group have shown that substitution of the central CC of TTF by Ni has a large effect on the L and NLO properties. , The resulting bis­(ethylene-1,2-dithiolato)­nickel (NiBDT) has many interesting properties (e.g., photochemical and thermal stability, tunable properties), due to which it is considered to be a very promising material. Several theoretical studies have also shown that lithiation may lead to a significant increase of the second hyperpolarizability. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the orbital overlap for HOMO reflects π–π stacking interaction between superimposed B/N-PLYs, which is conducive to intra- and intermolecular CT transitions from B-PLY to N-PLY. Further, the transition density matrix (TDM) , and the charge density difference maps (CDDMs) of dominant electron transitions are investigated for systems 2 , 3 , and 2 2 (Figures S3 and S4), providing valuable evidence for the above discussions.…”
Section: Resultsmentioning
confidence: 99%